(untitled) (Journal of Business Management and Accounting, 2024)
This abstract presents a significant study focusing on employee motivation and its impact on the HR Division of PT TIMAH Tbk. The emphasis on the importance of quality human resources as prime movers for company success is commendable. The research’s quantitative data analysis using regression and hypothesis testing with SPSS ensures robust findings. Excited to see the presentation as it will shed light on how compensation factors and work period influence employee motivation, with the potential to positively impact the progress and productivity of the company. The study’s practical implications, urging companies to consider compensation and work period when calculating employee rewards, will undoubtedly contribute to enhancing employee motivation and overall organizational performance. This research is a valuable addition to a conference program.